The Role of Leptin in Antipsychotic-Induced Weight Gain: Genetic and Non-Genetic Factors - Fabio Panariello; Gina Polsinelli; Carol Borlido; Marcellino Monda; Vincenzo De Luca (Journal of Obesity)
Schizophrenia is a chronic and disabling mental illness affecting millions of people worldwide. A greater proportion of people with schizophrenia tends to be overweight. Antipsychotic medications have been considered the primary risk factor for obesity in schizophrenia, although the mechanisms by which they increase weight and produce metabolic disturbances are unclear. Several lines of research indicate that leptin could be a good candidate involved in pathways linking antipsychotic treatment and weight gain. Leptin is a circulating hormone released by adipocytes in response to increased fat deposition to regulate body weight, acting through receptors in the hypothalamus. In this work, we reviewed preclinical, clinical, and genetic data in order to infer the potential role played by leptin in antipsychotic-induced weight gain considering two main hypotheses: (1) leptin is an epiphenomenon of weight gain; (2) leptin is a consequence of antipsychotic-induced “leptin-resistance status,” causing weight gain.